From "Real Rape" to Real Justice? Reflections on the Efficacy of More Than 35 years of Feminism, Activism and Law Reform - McDonald, Elisabeth (Victoria University of Wellington Law Review, 2014)
In this article, the author develops her observations made during the 2012 Suffrage Lecture at the University of Otago. Using the lecture as the starting point, the article considers what law reform over more than 35 years has actually achieved, with a specific focus on the admissibility of evidence about a complainant's previous sexual experience in a criminal case involving rape allegations. It concludes that although policy makers and legislators have been responsive to the concerns expressed by complainants about their treatment in the trial process, little real change to that experience has occurred. More fundamental work needs to be done by way of preventative education, challenging rape mythology and developing new processes to resolve allegations of sexual offending. These are the challenges for the next 35 years.